Topos of the Jewish treasure in postwar Polish, Belarusian and Ukrainian shtetls - Waligórska, Magdalena (Holocaust studies, 2025)
While the fascination with ‘Jewish gold’ and the belief that Jews possess riches long predates the Holocaust, it was the systematic dispossession of Jews during World War II that fueled the myth of ‘Jewish treasures’ to an unprecedented extent. Based on ethnographic field research in six former shtetls: Iŭje and Mir in Belarus, Biłgoraj and Izbica in Poland and Brody and Berezne in Ukraine, and diverse sources, including testimonies of survivors, archival documents, memoirs, and literary texts, this paper discusses the longevity of the myth of Jewish treasures in the post-Holocaust East-Central European provinces and analyses its social consequences.